The Call of Simon Peter in Luke 5,1-11: A Lukan Invention? - Szkredka, Slawomir (The Biblical Annals, 2018)
Recent studies on the role of the eyewitnesses in the formation of the Gospel tradition argue for the singular importance of the original followers of Jesus. Luke himself might reflect their unique standing with his stated reliance on “the eyewitnesses and the servants of the word” (1,2). Still, Luke’s expansion of the Markan call of Peter seems, to many modern scholars at least, precisely that – a literary reworking of the original Markan story. Luke thus appears to resort to literary fiction to confirm the authority of those who guarantee the non-fictional character of his narrative. The conflicting nature of this operation needs to be reexamined. As this article argues, the recent studies on the Lake of Galilee, Simon Peter, and the role of the eyewitnesses offer enough evidence to suggest that in composing the story of the call of Peter, Luke relied on a source that depicted the call in connection with the fishing miracle. Secondly, existence of such a tradition opens new possibilities for reconstructing the past so differently narrativized by Luke and Mark.